Análise da efetividade de programas de afastamento para cursos de pós-graduação stricto sensu em instituições públicas de ensino - Dias, Camila Gonçalves Campos (2023)
The theme of personnel development in public administration has gained prominence in recent years. The National Policy for the Development of People of the direct, autarchic and foundational federal public administration was created with the objective of promoting the development of public servants, aiming at improving the efficiency, effectiveness and quality of public services provided to citizens. However, even with the implementation of this policy, public institutions are unable to continuously promote the development of public servents in the necessary skills to achieve excellence in the performance of their position. In this context, many public servants have sought other academic training in addition to initial training, requesting, in some cases, complete withdrawal from their activities. In this work, it is proposed to analyze the effectiveness of personnel development programs through institutional indicators in a public educational institution. The theoretical contribution is focused in research on governance, personnel development and the Kirkpatrick model. The methodological procedure consists of a descriptive-exploratory research, with a qualitative approach, using the case study, where the studied population was constituted by the set of employees away for master's, doctoral and/or post-doctoral studies of a federal educational institution. Data were collected through access to the systems and database of the People Management sector of the researched institution. After the initial survey, a questionnaire was applied to the group identified for the research. With the results of the study, it was possible to identify the need and satisfaction of the public servants in the absence to perform stricto sensu graduate, both for the acquisition and expansion of knowledge and skills, in addition to the applicability of this knowledge in the institute. From the results, the technical product elaborated consists of a Post#Leave Evaluation Report for Stricto Sensu Graduate Courses designed based on the Kirkpatrick Model, which aims to evaluate the effectiveness of training and development programs, as well as an Institutional Development Panel, intending to collaborate with information for the Governance in Numbers Platform (GeN), responsible for the visualization and analysis of Ifes management indicators.